1987
DOI: 10.1037/h0085749
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational family relationships: An evaluation of theory and measurement.

Abstract: This article investigated the theory and measurement of inter generational family processes with the Personal Authority in the Family System Questionnaire and their relationship to life stress and health distress. Family process variables accounted for 53% of the variance in health distress in an adult clinical sample. For a collegeaged nonclinical sample, family process variables accounted for a significant amount of variance in health distress over and above life stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1
5

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 41 publications
4
48
1
5
Order By: Relevance
“…Of the various constructs that compose Bowen Theory, differentiation of self is the most critical to mature development and psychological health. Higher levels of differentiation of self have been linked with better psychological adjustment in adulthood (e.g., Bray, Harvey & Williamson, 1987;Greene, Hamilton & Rolling, 1986;Jenkins, Buboltz, Schwartz & Johnson, 2005), greater capacity for emotional self-regulation, self regulation of attention and behavior, adult attachment security (e.g., Skowron & Dendy, 2004;Skowron, Holmes & Sabatelli, 2003;Thorberg & Lyvers, 2006;Wei, Vogel, Ku & Zakalik, 2005), and fewer psychological symptoms and relationship difficulties (e.g., Bartle-Haring, 1997;Bartle-Haring & Gregory 2003;Peleg, 2002;Schwartz, Thigpen & Montgomery, 2006;Skowron, 2000;Skowron & Friedlander, 1998;Skowron, Stanley & Shapiro, 2009). Studies have also shown that higher levels of differentiation of self are linked to greater marital satisfaction among heterosexual and same-sex couples (e.g., Kosek, 1998;Montes-Berges, 2009;Parsons, Nalbone, Killmer &Wetchler, 2007;Peleg, 2008;Skowron, 2000;Spencer & Brown, 2007), and adults who report greater differentiation of self are at lower risk for engaging in child abuse and other forms of family violence (Skowron, Kozlowski, & Pincus, 2010;Skowron & Platt, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Of the various constructs that compose Bowen Theory, differentiation of self is the most critical to mature development and psychological health. Higher levels of differentiation of self have been linked with better psychological adjustment in adulthood (e.g., Bray, Harvey & Williamson, 1987;Greene, Hamilton & Rolling, 1986;Jenkins, Buboltz, Schwartz & Johnson, 2005), greater capacity for emotional self-regulation, self regulation of attention and behavior, adult attachment security (e.g., Skowron & Dendy, 2004;Skowron, Holmes & Sabatelli, 2003;Thorberg & Lyvers, 2006;Wei, Vogel, Ku & Zakalik, 2005), and fewer psychological symptoms and relationship difficulties (e.g., Bartle-Haring, 1997;Bartle-Haring & Gregory 2003;Peleg, 2002;Schwartz, Thigpen & Montgomery, 2006;Skowron, 2000;Skowron & Friedlander, 1998;Skowron, Stanley & Shapiro, 2009). Studies have also shown that higher levels of differentiation of self are linked to greater marital satisfaction among heterosexual and same-sex couples (e.g., Kosek, 1998;Montes-Berges, 2009;Parsons, Nalbone, Killmer &Wetchler, 2007;Peleg, 2008;Skowron, 2000;Spencer & Brown, 2007), and adults who report greater differentiation of self are at lower risk for engaging in child abuse and other forms of family violence (Skowron, Kozlowski, & Pincus, 2010;Skowron & Platt, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A PAFS fogalmait vizsgáló kutatások feltárták, hogy az intergenerációs családi folyamatok alapvetõen befolyásolják a családtagok egészségét, illetve stressztûrõ képességét (Bray, Harvey, & Williamson, 1987), a pszichológiai distressz megélését (Harvey és mtsai, 1991), az egészséggel kapcsolatos viselkedésmintákat , az identitás, autonómia, önbizalom, önuralom mértékét (Anderson & Fleming, 1986a, b), továbbá a kodependencia megjelenését (Prest, Benson, & Protinsky, 1998), a követ-kezõ generáció kapcsolati mintáit (Lawson & Brossart, 2001).…”
Section: A Személyes Autoritás a Családi Rendszerben Elméleteunclassified
“…En conséquence, les relations avec les parents sont reproduites avec le conjoint, les enfants et autres personnes significatives (Bray, Harvey, & Williamson, 1987;Williamson, 1991). Williamson (1991) maintient que l'équilibre entre ces deux processus est crucial pour la santé relationnelle à l'intérieur et à l'extérieur de la famille d'origine.…”
Section: Facteurs Liés Aux Changements De La Qualité De La Relation Cunclassified
“…Outre ces associations significatives à diverses composantes de la vie conjugale, la qualité des liens intergénérationnels tels que mesurés par le PAFS-Q est significativement associée à la qualité du développement général du jeune adulte (Johnson & McNeil, 1998;Johnson & Nelson, 1998) mais aussi de l'adulte plus mature (Cebik, 1988;JRabin, Bressler, &J?rager, 1993). Chez le jeune adulte, de meilleurs liens intergénérationnels sont liés à une adaptation accrue face aux situations stressantes (West, Gintner, & Zarski, 1989), à une meilleure estime de soi (Protinsky & Kilkey, 1996), à une augmentation de l'ajustement collégial (Protinsky & Kilkey, 1996;Smith, Ray, Wetchler, & Mihail, 1998), à une perception subjective plus positive de l'état de santé (Bray, Harvey, & Williamson, 1987;Protinsky & Kilkey, 1996) et à une plus grande aisance dans le processus de décision vocationnelle .…”
Section: Hypothèses De Rechercheunclassified
See 1 more Smart Citation